Performance and Mapping of the Scientific Production of the Rock-Soil-Vegetation Relationship - Galván-Alonso, María Nereida; Bravo-Vinaja, Ángel; Martínez-Montoya, Juan Felipe; Palacio-Núñez, Jorge; Noyola-Medrano, Ma. Cristina (REVISTA TERRA LATINOAMERICANA, 2024)
The relationship among rock, soil and vegetation is fundamental. Soils formed by weathering and rock erosion influenced by edaphic processes (carbonation, gypsification, salinization, among others) provide the essential substrate for plant life. Therefore, the purpose of the present research is to measure scientific production performance regarding the relationship among rock, soil and vegetation. In this manner, under the scientific approach used in this topic, its evolution and possible areas of future research, e.g. soil genesis, taxonomy, calcicolous, seleniferous, gypsophilous plants. This bibliometric analysis covers scientific production from 1935 to 2023, indexed in the Web of Science database. A total of 276 scientific papers were analyzed using uni and multidimensional bibliometric indicators. It was notable that 28% of these papers (77 in total) were published in the last four years, indicating a significant growth in this subject. The countries with the highest contribution were the United States (19.6%), China (18.1%), France (8.3%), Brazil (7.6%) and Australia (6.2%). The journal Catena led the production of these papers, and the most prominent author was Wang Kelin. The main themes of the rock-soil-vegetation relationship focused on: plant adaptation to heavy metal contaminated soils, nutrient availability, vegetation-rock relationship, restoration, plant diversity and soil organic matter content. This analysis highlights the sources of interest in the study of this relationship, in addition to those mentioned in the previous paragraph, rock and quality of the soil generated, capacity for use, potential use for certain plants, among.